BEHAVIORAL ASPECTS OF MAKING FINANCIAL DECISIONS IN CONDITIONS OF THE PANDEMIC: LOCAL LEVEL - VOZNYAK, Halyna; PATYTSKA, Khrystyna (Scientific journal «World of Finance», 2021)
Introduction. The established quarantine and social distancing have resulted in falling financial capacity of territorial communities, growing unemployment among the population, mass bankruptcy of enterprises, and changes in economic entities’ behavior. It makes the issue of determining behavioral aspects of making financial decisions and their adjustment to the impact of the coronavirus crisis of utmost importance because the overcoming of the coronavirus crisis by economic entities depends on the adaptation of their vital activity to new conditions. The purpose of the article is to outline the behavioral aspects of making financial decisions on a local level in conditions of the pandemic. Methods. The research is based on the use of dialectical analysis, synthesis, analogy, and logical generalization, as well as comparison and formalization. Results. The research has resulted in substantiation of the expediency of considering the coronavirus crisis in the context of the philosophical idea of black swan and an approach to the analysis of economic entities’ behavior as a reaction to uncertainty. The factors impacting the collective behavior in territorial communities are identified (social norms, social identity, collective memory, system of values, social inequality, economic conditions). The additional factors that determine the collective behavior in conditions of the pandemic are outlined (use of various information sources, discrepancies between forecasts, lack of evidence, high scientific uncertainty, times frame). The mistakes in cognitive processes of economic entities in territorial communities caused by the coronavirus crisis consequences are revealed. The features of making financial decisions in the process of managing the development of territorial communities in conditions of the pandemic are determined.